2019
DOI: 10.1186/s40563-019-0123-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the adhesive joints’ strength of the similar and dissimilar systems of metal alloy/polymer composite

Abstract: Bonding technology is one of the most popular methods of joining various constructional materials [1-3]. It plays a vital role in production of different types of machines and tools [2]. This fact results from numerous advantages of the adhesive joints. The most important ones include the capacity of joining construction materials of different physical and chemical properties [4-6], as well as of significantly different sizes (e.g. thickness) [4, 7-9]. A lot of advantages of the adhesive joints have contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
2
11
0
1
Order By: Relevance
“…These results, taking into account the type of adhesive, also confirm the results of research received by the authors in the work of [34]. Rudawska [34] emphasized that the use of more flexible adhesive in the case of a rough surface leads to greater adhesive joint strength (of aluminium alloys) than the use of more rigid adhesive.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results, taking into account the type of adhesive, also confirm the results of research received by the authors in the work of [34]. Rudawska [34] emphasized that the use of more flexible adhesive in the case of a rough surface leads to greater adhesive joint strength (of aluminium alloys) than the use of more rigid adhesive.…”
Section: Discussionsupporting
confidence: 84%
“…These results, taking into account the type of adhesive, also confirm the results of research received by the authors in the work of [34]. Rudawska [34] emphasized that the use of more flexible adhesive in the case of a rough surface leads to greater adhesive joint strength (of aluminium alloys) than the use of more rigid adhesive. According to da Silva and Lopes [35], an ideal adhesive joints is one in which the adhesive flexibility and strength properties vary along the overlap length, and they investigated the mixed-adhesive technique (various type of adhesive for preparing the adhesive joints).…”
Section: Discussionsupporting
confidence: 84%
“…Reducing the resin concentration within the layers of glass fibre lamination increases the vacuum pressure, consequently, increases the strength of dissimilar lap shear joint. Rudawska [52] concluded that a similar and dissimilar joint could have higher strength with ductile adhesives in comparison to brittle adhesives. This can be justified with larger plasticisation in the ductile adhesive, which can redistribute the load and make use of the less stressed parts of the overlap.…”
Section: Tensile Loadingmentioning
confidence: 99%
“…In recent years the connection of different materials has become more and more popular due to the development, in particular, of composite materials and bonding techniques. The number of such solutions has increased drastically in many industries, particularly in the automotive or aviation industry and others and is reflected by the growing year-to-year number of papers [30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…The significant influence on the joint strength has a suitable selection of the adhesive material. Such effects for the AW-7075 aluminum alloy with aramid-epoxy and carbon-epoxy composite joints were studied by Rudawska [37], Wang Z.Y. with coworkers [30,31] or Aljabar [33].…”
Section: Introductionmentioning
confidence: 99%